Circulating levels and the bioactivity of miR-30b increase during pubertal progression in boys - Mørup, Nina; Stakaitis, Rytis; Main, Ailsa Maria; Golubickaite, Ieva; Hagen, Casper P.; Juul, Anders; Almstrup, Kristian (Frontiers in Endocrinology, 2023)
Background: Puberty marks the transition from childhood to adulthood and is initiated by activation of a pulsatile GnRH secretion from the hypothalamus. MKRN3 functions as a pre-pubertal break on the GnRH pulse generator and hypothalamic expression and circulating levels of MKRN3 decrease peri-pubertally. In rodents, microRNA miR-30b seems to directly target hypothalamic MKRN3 expression – and in boys, circulating levels of miR-30b-5p increase when puberty is pharmacologically induced. Similarly, miR-200b-3p and miR-155-5p have been suggested to inhibit expression of other proteins potentially involved in the regulation of GnRH secretion. Here we measure circulating levels of these three miRNAs as boys progress through puberty. Materials and Methods: Forty-six boys from the longitudinal part of the Copenhagen Puberty Study were included. All boys underwent successive clinical examinations including estimation of testis size by palpation. miR-30b-5p, miR-200b-3p, and miR-155-5p were measured in serum by RT-qPCR using a kit sensitive to the phosphorylation status of the miRNAs. Thirty-nine boys had miRNA levels measured in three consecutive samples (pre-, peri-, and post-pubertally) and seven boys had miR-30b-5p levels measured in ten consecutive samples during the pubertal transition. Results: When circulating levels of miR-30b-5p in pre- and peri-pubertal samples were compared with post-pubertal levels, we observed a significant increase of 2.3 and 2.2-fold (p-value <6.0×10-4), respectively, and a larger fraction of miR-30b-5p appeared to be phosphorylated post-pubertally indicating an increase in its bioactivity. We also observed a negative correlation between circulating levels of miR-30b-5p and MKRN3. The inter-individual variation in circulating miR-30b levels was substantial and we could not define a clinical threshold for miR-30b-5p suggestive of imminent puberty. Also, miR-155-5p showed significantly increasing levels from the peri- to the post-pubertal stage (p=3.0×10-3), whereas miR-200b-3p did not consistently increase. Conclusion: Both circulating levels of miR-30b-5p and its bioactivity increase during the pubertal transition in boys supporting its role in the activation of the HPG axis at the onset of physiologically normal puberty.